Compensation policies across EU countries: Different pay practices for similar outcomes - Duarte, H.; Suleman, F.; Suleman, A. (EURAM 2019 Conference, 2019)
This study contributes to the research on comparative institutional human resource management literature and provides empirical evidence on the relationship between compensation policy and models of capitalism. More specifically, it tries to classify firms according to their compensation policies and check for the similarities and differences among firms in each model of varieties of capitalism (VoC). We draw on Structure of Earnings Survey (SES) data for 2014, which provide information on pay variables on eighteen European countries. Empirical strategy comprises two steps. The analysis starts with a fuzzy clustering to identify typical compensation policies of the sampled countries. In the next step, we estimate a Tobit regression model to examine how the compensation policy interacts with the model of VoC proposal. The multivariate data analysis pointed to four fuzzy clusters based on the level of internal dispersion of earnings and relation to the market. Four fuzzy clusters of compensation policies can be ranged from low to high dispersion, while the other represents a policy oriented to the market. Internal Labour Market Undifferentiated (ILMU) policy show a negligible dispersion of earnings either within or between job levels; firms pay wages below the market rate and have lower returns to education and tenure. In the Internal Labour Market Qualified (ILMQ) policy, the key features are the highest return to education and tenure. The cluster labelled as Competitive evidences moderate dispersion and a wage rate higher than the general and industry market rates. Finally in the Incentive policy all the dispersion variables show the highest values. These findings illustrate the variety of pay practices that seem to target a single outcome, the individualisation of earnings. While, some firms use within and between job dispersion to reward high-performers, others providehigh return to education and qualifications. Some sampled firms prefer to be attractive in the market and pay higher wages, and offer at same time merit pay systems. The Tobit regression model estimates show that highly dispersed policies prevail in Liberal labour market, while low dispersion policies are associated with Coordinated Markets Economy. The findings help dividing the Continental versus Southern and Transition European countries. In the former prevails Competitive and Incentive policies, while in the latter we found mixed patterns of ILMU and ILMQ. These results unveil the influence of labour market institutions, legal settings and probably cultural environments implicit in the capitalism model.